2018
DOI: 10.1002/aenm.201802398
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Cellulose Nanofiber Enabled Thick Electrode for Compact and Flexible Energy Storage Devices

Abstract: the current collector. Recently, progresses have been made in thick electrode architecture design by incorporating external magnetic fields and carbon templates for fast charge transfer kinetics, but the complicated producing processes and fragile electrode mechanical properties limit their ability for practical applications. [10][11][12][13][14][15] Fiber like carbon materials with large aspect ratio, such as carbon nanotubes (CNT), can significantly improve electrode mechanical strength and energy density du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
137
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(139 citation statements)
references
References 47 publications
1
137
0
1
Order By: Relevance
“…Moreover, the magnified SEM image (Figure 3e) and corresponding elemental mapping results (Figure 3f) illustrate that the networks of AgNWs and MnONWs are interpenetrated and homogeneously distributed on the 3D scaffold. The interpenetration between the highly conductive AgNW network and the scaffold of electrochemically active materials may enable rapid, stable, and homogenous charge transfer throughout the entire depth of the electrode, which increases the areal power density of the assembled MSC device . Thanks to the introduction of AgNW networks, the conductivity of the MXene‐AgNW‐MnONW‐C60 nanocomposite films was measured to be as high as 10 970 S cm −1 (Figure S4, Supporting Information), approximately three times higher than that of the pure MXene film, and also higher than that of any previously reported printable electrode inks for MSCs .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the magnified SEM image (Figure 3e) and corresponding elemental mapping results (Figure 3f) illustrate that the networks of AgNWs and MnONWs are interpenetrated and homogeneously distributed on the 3D scaffold. The interpenetration between the highly conductive AgNW network and the scaffold of electrochemically active materials may enable rapid, stable, and homogenous charge transfer throughout the entire depth of the electrode, which increases the areal power density of the assembled MSC device . Thanks to the introduction of AgNW networks, the conductivity of the MXene‐AgNW‐MnONW‐C60 nanocomposite films was measured to be as high as 10 970 S cm −1 (Figure S4, Supporting Information), approximately three times higher than that of the pure MXene film, and also higher than that of any previously reported printable electrode inks for MSCs .…”
Section: Resultsmentioning
confidence: 99%
“…From the view point of production cost and capacity, cellulose, the most abundant natural polymer on earth, is highly competitive and attractive as a 1D building block for constructing thick electrodes . Recently, Kuang et al reported a highly conductive hybrid fiber based on abundantly available cellulose nanofibers (CNFs) and commercialized CBs as a 1D building block for constructing free‐standing thick electrodes ( Figure 8 a) . The hybrid fibers were readily prepared by the conformal electrostatic assembly of neutral CBs on negatively charged CNFs, ensuring and efficient space packing of the CBs with low interface resistance.…”
Section: Integrated Electrode and Current Collectormentioning
confidence: 99%
“…e) Areal and volumetric capacity comparisons of the nanopaper electrode and the conventional electrode under different active mass loadings. Reproduced with permission . Copyright 2018, John Wiley and Sons.…”
Section: Integrated Electrode and Current Collectormentioning
confidence: 99%
“…However, the optimized free-standing electrode exhibit lower energy density and inferior rate capability than conventional electrode. Kuang et al (2018) prepared a nanopaper electrode with compact structure and high mass loading (up to 60 mg/cm 2 ), in which conductive nanofiber (CNF) network is designed with decoupled electron and ion transfer pathways via electrostatic assembly of neutral CB particles on negatively charged CNF. Wang et al (2018a) made a folded GR high areal capacity composite electrode by a water-facilitated folding method.…”
Section: Freestanding Electrodesmentioning
confidence: 99%